Behaviour of Captive Ostriches (Struthio camelus) at Universiti Malaysia Kelantan, Bachok Campus, Kelantan, Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
The behavioural patterns of six captive ostriches (Struthio camelus) werestudied at Universiti Malaysia Kelantan, Bachok Campus between July andSeptember 2014. The main purpose of the study was to determine thebehavioural patterns of ostriches in captivity to provide the useful informationfor better management action. The ostriches were observed daily for 11 hoursfrom 0700 hrs until 1800 hrs for 45 days by using the focal sampling technique.Six categories of behavioural patterns were observed namely resting,locomotion, ingestive, comfort, aggression and thermoregulation. The highestbehaviour observed was walking compared to other behaviours, while thelowest was running. The result of the study showed a significant difference ofbehavioural patterns of captive ostriches between different observationalperiods except for locomotion and aggression behaviours. The finding of thestudy showed that ostriches reared in captivity possessed similar behaviouralpatterns to those remaining in the wild, although some captive circumstancesimposed minor differences.
Keywords: Captive ostriches; behavioural patterns; Bachok Campus; Kelantan; Malaysia